Glucagon-like peptide-1 (GLP-1) raises blood-brain glucose transfer capacity and hexokinase activity in human brain - Gejl, Michael; Lerche, Susanne; Egefjord, Lærke; Brock, Birgitte; Møller, Niels; Vang, Kim; Rodell, Anders B.; Bibby, Bo M.; Holst, Jens J.; rungby, Jørgen; Gjedde, Albert (Frontiers in Neuroenergetics, 2013)
In hyperglycemia, glucagon-like peptide-1 (GLP-1) lowers brain glucose concentration together with increased net blood-brain clearance and brain metabolism, but it is not known whether this effect depends on the prevailing plasma glucose (PG) concentration. In hypoglycemia, glucose depletion potentially impairs brain function. Here, we test the hypothesis that GLP-1 exacerbates the effect of hypoglycemia. To test the hypothesis, we determined glucose transport and consumption rates in seven healthy men in a randomized, double-blinded placebo-controlled cross-over experimental design. The acute effect of GLP-1 on glucose transfer in the brain was measured by positron emission tomography (PET) during a hypoglycemic clamp (3 mM plasma glucose) with 18F-fluoro-2-deoxy-glucose (FDG) as tracer of glucose. In addition, we jointly analyzed cerebrometabolic effects of GLP-1 from the present hypoglycemia study and our previous hyperglycemia study to estimate the Michaelis-Menten constants of glucose transport and metabolism. The GLP-1 treatment lowered the vascular volume of brain tissue. Loading data from hypo- to hyperglycemia into the Michaelis-Menten equation, we found increased maximum phosphorylation velocity (Vmax) in the gray matter regions of cerebral cortex, thalamus, and cerebellum, as well as increased blood-brain glucose transport capacity (Tmax) in gray matter, white matter, cortex, thalamus, and cerebellum. In hypoglycemia, GLP-1 had no effects on net glucose metabolism, brain glucose concentration, or blood-brain glucose transport. Neither hexokinase nor transporter affinities varied significantly with treatment in any region. We conclude that GLP-1 changes blood-brain glucose transfer and brain glucose metabolic rates in a PG concentration-dependent manner. One consequence is that hypoglycemia eliminates these effects of GLP-1 on brain glucose homeostasis.